The mid-infrared Leavitt law for classical Cepheids in the Magellanic Clouds. Issue 1 (27th October 2020) - Chown, Abigail H; Scowcroft, Victoria; Wuyts, Stijn
ABSTRACT: The Cepheid Leavitt Law (LL), also known as the Period–Luminosity relation, is a crucial tool for assembling the cosmic distance ladder. By combining data from the OGLE-IV catalogue with mid-infrared photometry from the Spitzer Space Telescope, we have determined the 3.6 and 4.5 $μ$ m LLs for the Magellanic Clouds using ∼5000 fundamental-mode classical Cepheids. Mean magnitudes were determined using a Monte Carlo Markov Chain (MCMC) template fitting procedure, with template light curves constructed from a subsample of these Cepheids with fully phased, well-sampled light curves. The dependence of the Large Magellanic Cloud LL coefficients on various period cuts was tested, in addition to the linearity of the relationship. The zero-point of the LL was calibrated using the parallaxes of Milky Way Cepheids from the Hubble Space Telescope and Gaia Data Release 2. Our final calibrated relations are M [3.6] = −3.246(±0.008)(log ( P ) − 1.0) − 5.784(±0.030) and M [4.5] = −3.162(±0.008)(log ( P ) − 1.0) − 5.751(±0.030).